EFEK MODERASI TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT - Lona Noviani; Rohaelis Nuraisiah; Anggi Haerani (FKIP, Universitas Banten Jaya, 2021)
This study aims to examine the effect of due professional care, experience and accountability on audit quality with the moderation of the time budget of pressure. The study was conducted at 17 KAP Banten Province with a total sample of 52 respondents. Data analysis used the SEM-PLS method by testing the measurement model and structural model. The results of hypothesis testing show that due professional care has a positive effect on audit quality, so the higher the auditor performs due professional care, the better the audit quality will be. Experience has a positive effect on audit quality, so the more experienced the auditor is in carrying out his duties, the better the audit quality will be. Accountability has a positive effect on audit quality, so that auditors who carry out accountability well can make their audit results more qualified. There is no moderation of time budget of pressure on the effect of due professional care on audit quality. Time budget of pressure will not interfere with the quality of audits produced by professional auditors. There is no moderation of time budget of pressure on the effect of experience on audit quality. Time budget of pressure will not interfere with audit quality resulting from auditors who have high experience in conducting audits. There is no moderation of time budget of pressure on accountability to audit quality. Auditors with high accountability are not bothered by time budget of pressure in producing high audit quality.